Perancangan Showroom Mobil Mini di Surabaya - Lintu Tulistyantoro, Darren Louis Cahyadi (Intra, 2016)
MINI is a small car produced by the British Motor Corporation (BMC) and its successors from 1959 until 2000. The original model of the car is considered as the icon of the British in the 1960s. The design concept in this design is